LITERASI KREATIF: MEMBANGUN KETERAMPILAN ABAD 21 MELALUI PEMBELAJARAN SEJARAH LOKAL KESULTANAN LANGKAT - Tanjung, Septiansyah; Supriatna, Nana (Harmony: Jurnal Pembelajaran IPS dan PKN, 2021)
The development of the digital era has brought many changes in human life, including the transformation of education and literacy. Literacy further develops into a basic skill to be able to compete amid today's globalizations. It is also an important competency to be developed for students through the learning process. Creative pedagogy is a solution to solving this problem where students have creative potential that must be supported to be developed. Through learning the local history of Langkat Sultanate, a creative pedagogical approach can be applied by combining the use of literacy to carry out learning. By using literature study, the author constructs the discussion in this article to obtain a meaningful picture of how to apply creative pedagogy and literacy learning in learning the local history of the Langkat Sultanate. The integration of these approaches produces creative literacy concepts that provide opportunities for students to develop multicompetence such as 21st-century and literacy skills, including digital literacy. These skills are very relevant to the goals of education to create human resources who are intelligent, competitive, and have character. Perkembangan era digital telah memberi banyak perubahan dalam kehidupan manusia termasuk transformasi pendidikan dan literasi. Literasi lebih lanjut berkembang menjadi suatu kecakapan dasar untuk dapat bersaing ditengah globalisasi dimasa ini. Selain itu, kreativitas menjadi kompetensi penting yang harus dikembangkan kepada peserta didik melalui proses pembelajaran. Pedagogi kreatif menjadi solusi untuk memecahkan persoalan tersebut dimana peserta didik memiliki potensi kreatif yang harus didukung untuk dikembangkan. Melalui pembelajaran sejarah lokal Kesultanan Langkat, pendekatan pedagogi kreatif dapat diterapkan dengan memadukan penggunaan literasi untuk melaksanakan pembelajaran. Dengan menggunakan studi literatur, Penulis mengkonstruksi pembahasan dalam artikel ini untuk mendapatkan gambaran bermakna bagaimana menerapkan pedagogi kreatif dan pembelajaran literasi dalam pembelajaran sejarah lokal Kesultanan Langkat. Integrasi dari sejumlah pendekatan tersebut menghasilkan konsep literasi kreatif yang memberikan kesempatan kepada peserta didik untuk mengembangkan multikompetensi seperti keterampilan abad 21 dan keterampilan literasi, termasuk literasi digital. Kecakapan tersebut sangat relevan dengan tujuan pendidikan untuk menciptakan sumber daya manusia cerdas, kompetitif, dan berkarakter.